한국 여수 인근 무인도 해역에서 굴 Crassostrea gigas의 인터섹스 출현율 - 박정준; 신소령; 김현진; 오한영; 이동근; 이정식; Park, Jung Jun; Shin, So Ryung; Kim, Hyeon Jin; Oh, Han Young; Lee, Dong-Geun; Lee, Jung Sick (한국해양생명과학회지, 2021)
The purpose of this study was to report the intersex identified in the oyster Crassostrea gigas (n=410, SH 43.3±11.4 mm) in the waters around 13 uninhabited islands near Yeosu. The overall sex ratio (male: female) was 1:1.1, but there was a difference between the sampling areas. In Gajangdo, Sogyeongdo, and Jungsamdo, females showed a high ratio of 65% or more, and in Songdo, Chodo, and Buseodo, males showed a high ratio of 65% or more. The overall intersexuality was about 12.8%, which was high in males, about 34.7% in females and 64.3% in males. Intersexuality was the highest with about 43.8% in Chodo of Gamak Bay. Histologically, intersex could be divided into three types: intrafollicular type, interfollicular type and mixed type. Among these three types, the intrafollicular type was the most dominant with about 81.6%. The intersex cause of oysters reported in this study is considered to require detailed research in the future. 본 연구는 여수 인근 13개 무인도 주변 해역의 굴 Crassostrea gigas (n=410, SH 43.3±11.4 mm)에서 확인된 인터섹스 현상을 보고하고자 하였다. 전체 성비(암:수)는 1:1.1이었으나 채집 정점별로 성비의 차이를 보였다. 가장도, 소경도, 중삼도에서는 암컷이 65% 이상의 높은 비율을 보였으며, 송도, 초도, 부서도에서는 수컷이 65% 이상의 높은 비율을 나타냈다. 전체 intersexuality 는 약 12.8%로 암컷에서 약 34.7%, 수컷에서 약 64.3%로 수컷에서 높았다. Intersexuality는 가막만의 초도에서 약 43.8%로 가장 높았다. 조직학적으로 인터섹스는 intrafollicular type, interfollicular type, mixed type의 세 가지 형태로 나눌 수 있었다. 이들 세 가지 형태 가운데 intrafollicular type이 약 81.6%로 가장 우세하였다. 본 연구에서 보고된 굴의 인터섹스 원인에 관해서는 추후 세부적인 연구가 필요할 것으로 생각된다.